Model Dinamika Sistem Logistik Bantuan Pasca Bencana Gempa Bumi–Tsunami di Kota Padang - Rika Ampuh Hadiguna; Agus Wibowo (UIN Sultan Syarif Kasim Riau, 2012)
This paper was discusses logistics management to help the victims of earthquake and tsunami disaster. Model development is performance based on case study in Kota Padang. Purpose of the study is to investigate the effect of operations behavioral of disaster relief logistics system after earthquake and Tsunami disaster in Padang using system dynamics simulation model. This study was build simulation model to analyze logistics relief operations of earthquake and tsunami disaster. Model development refers to the occurrence the earthquake disaster in Padang on September 30, 2009. Verification and validation of the proposed model is applying six scenarios. Limitation of funds in disaster relief operations was always deriving conflict of interest between infrastructure and commodities procurement. The simulation results were show that the allocation of disaster relief funds will reach the best effectiveness when government was allocated the relief budget to procure the commodities. The damage level that caused by earthquake or tsunami did not show a significant influence in achieving the best effectiveness in relief logistics operations.Keywords: disaster logistics, simulation, system dynamics